Pulmonary biology of anti-interleukin 5 antibodies - RW Egan; D Athwahl; C-C Chou; RW Chapman; S Emtage; C-H Jenh; TT Kung; PJ Mauser; NJ Murgolo; MW Bodmer (Memorias do Instituto Oswaldo Cruz, 1997)
Interleukin 5 (IL-5) is a critical cytokine for the maturation of eosinophil precursors to eosinophils in the bone marrow and those eosinophils then accumulate in the lungs during asthma. We have studied anti IL-5 antibodies on allergic responses in mice, guinea pigs and monkeys and are extending this experiment into humans with a humanized antibody. In a monkey model of pulmonary inflammation and airway hyperreactivity, we found that the TRFK-5 antibody blocked both responses for three months following a single dose of 0.3 mg/kg, i.v. This antibody also blocked lung eosinophilia in mice by inhibiting release from the bone marrow. To facilitate multiple dosing and to reduce immunogenicity in humans, we prepared Sch 55700, a humanized antibody against IL-5. Sch 55700 was also active against lung eosinophilia in allergic monkeys and mice and against pulmonary eosinophilia and airway hyperresponsiveness in guinea pigs. Furthermore, as opposed to steroids, Sch 55700 did not cause immunosuppression in guinea pigs. Studies with this antibody in humans will be critical to establishing the therapeutic potential of IL-5 inhibition.